2008
DOI: 10.1002/cncr.23245
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and survival in 1396 patients with uterine leiomyosarcomas

Abstract: BACKGROUND The objectives of the current study were to determine the prognostic factors associated with disease‐specific survival (DSS) and to analyze the role of lymphadenectomy (LND) and oophorectomy in the management of uterine leiomyosarcomas (LMS). METHODS Data were abstracted from the Surveillance, Epidemiology, and End Results database (1988–2003). Kaplan‐Meier and Cox proportional hazards regression models were used for analyses. RESULTS The median age of the 1396 patients was 52 years. There were 951 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
269
3
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(300 citation statements)
references
References 57 publications
16
269
3
12
Order By: Relevance
“…No consensus has been reached regarding the correlation between the clinical course of LMS and possible prognostic factors such as age, disease stage, tumor size, necrosis, vascular invasion, and mitotic index (2,9,(15)(16)(17). Most studies reported that tumor size and mitotic index are the most significant parameters for prognosis (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No consensus has been reached regarding the correlation between the clinical course of LMS and possible prognostic factors such as age, disease stage, tumor size, necrosis, vascular invasion, and mitotic index (2,9,(15)(16)(17). Most studies reported that tumor size and mitotic index are the most significant parameters for prognosis (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…For quantitatively evaluating Ki-67 staining, the five most intensively stained areas were selected while screening HPF at 40× magnification, and the average of these values was used (16).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Carcinosarcomas re tumors with a high capacity of extension: 37% of patients present myometrail invasion, 17% present nodal involvement and almost 21% of patients present malignant cells in the peritoneal lavage cytology. (3,4,5) In almost all cases the presence of the distant metastases is due to the epithelial component of the carcinosarcoma.…”
Section: Classification Of Uterine Sarcomasmentioning
confidence: 99%
“…Combining size tumor with the mitotic index, led to the classification of patients into three risk groups: low risk group (tumor size less than 100 mm and less than 10 mitoses / 10 high-resolution fields), medium-risk group (whether the tumor is larger than 100 mm, and no more than 10 mitoses / 10 fields) -risk of death 1.9 times higher, and high-risk group (tumor greater than 100 mm or a high index of mitosis) -risk of death by 5.3 times higher. (3,11,12) …”
Section: Uterine Leiomyosarcomasmentioning
confidence: 99%
“…However, debulking of any tumor outside the uterus should be a goal of the surgery since the most important prognostic factor is residual disease following primary surgery (1,4).…”
Section: Introductionmentioning
confidence: 99%